Mapping Aboveground Biomass of Four Typical Vegetation Types in the Poyang Lake Wetlands Based on Random Forest Modelling and Landsat Images - Wan, Rongrong; Wang, Peng; Wang, Xiaolong; Yao, Xin; Dai, Xue (Frontiers in Plant Science, 2019)
Wetland biomass is an important indicator of wetland ecosystem health. In this study, four dominant vegetation communities (Carex cinerascens, Phalaris arundinacea, Artemisia selengensis, and Miscanthus sacchariflorus) in the Poyang Lake wetland from 2010 to 2016 were classified from Landsat images using SID (Spectral Information Divergence). Significantly, we combined AGB (above-ground biomass) field measurements and remote sensing data to establish a suitable model for estimating wetland AGB in Poyang Lake, which is on the Ramsar Convention’s list of Wetlands of International Importance. The results show that (1) overall, the classification accuracy for vegetation pixels across five years ranged from 59.1% to 73.7%; and (2) the interannual and spatial variations in the AGB of the four vegetation types were clear. Carex cinerascens had an average AGB density value of 1.28 kg m-2 in Poyang Lake from 2010 to 2016; Miscanthus sacchariflorus had the highest AGB density with an average value of 1.39 kg m-2; Artemisia selengensis had almost the same level at 1.26 kg m-2; and Phalaris arundinacea had the lowest AGB density at 0.64 kg m-2. This study provides useful experience for estimating carbon sequestration of vegetation in freshwater wetlands.